Are Financial Statements More Comparable When GAAP Restricts Managers’ Discretion? - Young, Spencer (Management Science, 2023)
I examine whether financial statements are more comparable when accounting standards restrict managers’ discretion. My evidence suggests that restricting managers’ discretion is associated with reduced comparability, on average. This effect is strongest when transactions are dissimilar. To explore this relation, I develop novel measures of two distinct types of incomparability. I find that restricting managers’ discretion is associated with an increase in incomparability stemming from dissimilar transactions appearing overly similar. Together, these findings suggest that restricting managers’ discretion may be more harmful to comparability than is too much diversity in practice. However, I also find evidence that restricting managers’ discretion may enhance comparability in two scenarios. Specifically, I find that restricting managers’ discretion is associated with improved comparability when standards (1) restrict manipulation of financial reports and (2) eliminate dissimilar accounting treatments that do not reflect differences in the underlying transactions. Overall, these findings nuance our understanding of how the requirements imposed by standard setters influence financial statement comparability. This paper was accepted by Suraj Srinivasan, accounting. Funding: Financial support from The School of Accountancy at the University of Arizona and the John T. Steed School of Accounting at the University of Oklahoma is gratefully acknowledged. Supplemental Material: The internet appendix and data files are available at https://doi.org/10.1287/mnsc.2023.4961 .